Government Auditors' Capabilities to Detect Fraud and The Factors that Influence Them - Ngesti, Mella; Djamil, Nasrullah (InJEBA : International Journal of Economics, Business and Accounting, 2024)
Fraud is behavior that is contrary to the law carried out by individuals, both from within and outside the organization, with the intention of gaining personal or group benefit while harming other people. This research aims to determine the influence of professional skepticism, competence, independence and ethics on the auditor's ability to detect fraud. The variables of this research are professional skepticism, competence, independence and ethics as variable This research used census techniques, so the number of samples in this study was 56 people. Data analysis in this study used statistical analysis with Statistical Product and Service for Windows version 26.00 (SPSS version 26). The results of this research show that Professional Skepticism has a significant effect on the auditor's ability to detect fraud, Competence has a significant effect on the auditor's ability to detect fraud, Independence has a significant effect on the auditor's ability to detect fraud, Ethics has a significant effect on the auditor's ability to detect fraud.